Cesarean and VBAC rates among immigrant vs. native-born women: a retrospective observational study from Taiwan Cesarean delivery and VBAC among immigrant women in Taiwan - Fu Jung-Chung; Xirasagar Sudha; Liu Jihong; Probst Janice C (BMC, 2010)
Abstract Background Cultural and ethnic roots impact women's fertility and delivery preferences This study investigated whether the likelihood of cesarean delivery, primary cesarean, and vaginal delivery after cesarean (VBAC) varies by maternal national origin. Methods We conducted a nation-wide, population-based, observational study using secondary data from Taiwan. De-identified data were obtained on all 392,246 singleton live births (≥500 g; ≥20 weeks) born to native-born Taiwanese, Vietnamese and mainland Chinese-born mothers between January 1 2006 and December 31 2007 from Taiwan's nation-wide birth certificate data. Our analytic samples consisted of the following: for overall cesarean likelihood 392,246 births, primary cesarean 336,766 (excluding repeat cesarean and VBAC), and VBAC 55,480 births (excluding primary cesarean and vaginal births without previous cesarean). Our main outcome measures were the odds of cesarean delivery, primary cesarean delivery and VBAC for Vietnamese and Chinese immigrant mothers relative to Taiwanese mothers, using multiple regression analyses to adjust for maternal and neonatal characteristics, paternal age, institutional setting, and major obstetric complications. Results Unadjusted overall cesarean, primary cesarean, and VBAC rates were 33.9%, 23.0% and 4.0% for Taiwanese, 27.6%, 20.1% and 5.0% for mainland Chinese, and 19.3%, 13.9 and 6.1% for Vietnamese respectively. Adjusted for confounders, Vietnamese mothers were less likely than native-born Taiwanese to have overall and primary cesarean delivery (OR = 0.59 and 0.58 respectively), followed by Chinese mothers (both ORs = 0.90 relative to native-born Taiwanese). Vietnamese mothers were most likely to have successful VBAC (OR = 1.58), followed by Chinese mothers (OR = 1.25). Conclusion Immigrant Vietnamese and Chinese mothers have lower odds of cesarean and higher VBAC odds than native-born Taiwanese, consistent with lower cesarean rates prevailing in their home countries (Vietnam 10.1%; mainland China 20% - 50% rural and urban respectively).